VISUAL SIGNS ON MEGALITHIC STONES IN UMA BARA VILLAGE, IN EASTERN SUMBA, INDONESIA: A CULTURAL SEMIOTIC ANALYSIS - Tunggul, Jerimunsen; Tamelan, Thresia Magdalena; Jacob, June A. (English Education Study Program - Artha Wacana Christian University, 2023)
This paper explores the meaning of visual signs on megalithic stones in Uma Bara Village. Employing the theory of Ferdinand de Saussure on semiotics, the paper focused on the cultural semiotic analysis of visual signs. It is a descriptive qualitative study of cultural semiotics. The data was obtained from megalithic stones and a Wunangu 'a cultural practitioner' through observation and interview. The data analysis shows that there are 16 visual signs on megalithic stones in Uma Bara village. Each visual sign represents a Sumbanese cultural symbol. For example, the Njara Pakaliti statue ‘a statue of a horse ridden by its owner', represents unity. Thus, the meanings of the visual signs found in Uma Bara village have a close relationship with the socio-cultural of the Sumba people, especially in Uma Bara village